Implementasi Pembelajaran Lesson Study Pada Matakuliah Genetika - Mahrus Mahrus; Lalu Zulkifli; Syachruddin AR (Postgraduate, University of Mataram, 2019)
Abstract: The purpose of this study was to improve the results and learning process of Genetic subjects in the Biology Education Study Program through lesson study (LS). The research type is descriptive, the sampling technique used purposive. The study sample used 40 students in the sixth semester of class a Biology Education Study Program, Faculty of Education, University of Mataram in academic year 2017/2018. The research data collection technique used observation, documentation, and tests. Data on student learning outcomes and LS-based learning processes were analyzed descriptively. LS implementation in this study consisted of four cycles and each cycle consisted of three stages, namely: planning, implementation, and reflection. Classically the average value of students' cognitive achievement is 82.1% in cycle I and II while in cycle III and IV it increases to 82.67%. Data from LS implementation observation results obtained an average value of 91.63%. The conclusion of this study is the application of LS learning can improve student achievement and learning processes on Genetic subjects in the Biology Education Study Program. It is recommended to other researchers to conduct similar follow-up research in broader research areas, more samples, use more complex research designs, and use more subjects so that more optimal results can be found. Keywords: Lessons Study; learning; genetics; learning achievements; collaborative